The Influence of Perceived Value, Trust, and Payment Convenience on Digital Purchase Satisfaction of Food Delivery Application Users - Ibrahim, Mozart Malik; Risdwiyanto, Andriya; Violin, Vivid; Hanata, Reza Yonatan; Sidjabat, Sonya; Parandy, La Mema (Journal of Social Science and Business Studies, 2025)
This research is aimed to primarily figure out the impact of perceived value, trust, and payment convenience on the satisfaction of digital purchases among users of food delivery apps in Indonesia. The soaring market for digitally ordered food also makes one wonder what are the factors that lead to consumers' satisfaction with their purchases in the digital era. Researchers applied a quantitative explanatory method and gathered data through a questionnaire that was completed by 200 respondents who are regularly using food delivery services. The sample selection was carried out through purposive sampling. Findings indicate that the three independent variables, perceived value, trust, and payment convenience, to have a positive and significant influence on digital purchase satisfaction. Moreover, this study adds to the theory of digital marketing literature and provides some practical ideas to food delivery companies on how they can enhance customer experience by offering more value, trust, and payment convenience.